Excavations at Tiberias, 1989-1994 - Hirshfeld, Yizhar (IAA reports, 2004)
Pt. 1. The excavations at the sewage processing plant, 1989-1990. Architecture and stratigraphy / Yizhar Hirschfeld -- Mosaic floors / Rina Talgam -- Pottery and small finds / Roni Amir -- Coins / Rachel Milstein, Donald T. Ariel -- Glass and metal objects / Ayala Lester -- A bone figurine / Karen Singer -- pt. 2. the excavations on Mount Berenice, 1990-1994. Architecture and stratigraphy / Yizhar Hirschfeld -- Mosaics and frescoes / Roni Amir -- Pottery / Roni Amir -- Coins / Gabriela Bijovsky -- Glass and metal finds / Nitzan Amitai-Preiss -- Marble finds from the church / Lihi Habas, Roni Amir -- Spinder Whorls / Orit Shamir -- Early Bronze age I pottery / Raphael Greeberg -- The human skeletal remains / Yossi Nagar, Jacques Verdene -- Conclusions / Yizhar Hirschfeld -- Appendixes / Yizhar Hirschfeld.